Keterlibatan Emosional Siswa dalam Pembelajaran Membaca Pemahaman dengan Menggunakan Strategi Melempar Bola Salju - Rahayu, Sinta Dewi; loka, Nina Puspita; wati, Maya Rahma (Peneliti.net, 2024)
This study aimed to describes the students’ emotional engagement in learning reading comprehension through snowball throwing strategy. The method used in this research was qualitative approach with case study method. This study involved six students from class VIII-I and one English teacher junior high school in Karawang. The data was then analyzed using observations and interviews. The results of this study showed that the use of the Snowball Throwing Strategy for learning reading comprehension was found to be able to positively encourage students' emotional engagement in the context of reading comprehension, such as feeling happy enthusiastic, more confident student and can engage a positive teacher role in learning although there are drawbacks to snowball throwing strategy such as learning is little noisy when studying. Therefore, snowball throwing strategy seems to be recommended to be applied in reading comprehension learning.